Effects of Stress on Human Health - Çakmur, Hülya (IntechOpen, 2020)
Stress response is a physiological reaction of the human body to potential dangers (tangible or intangible). For a living organism, stress within physiological limits is necessary to stay alive. But the protective effects of stress can easily be potentially harmful for the body when it is out of control. Invariably, life events and stress are combined. It is well established that chronic and excessive stress may reduce the quality and duration of life. Even though the negative health consequences of stress may be physical or psychological, it has been observed that many people still maintain a disease-free lifespan after exposure to intensive stressful conditions. It can be inferred that some people have biologically and psychologically higher resilience capacity. However, there is no doubt that management of stress may be possible and could be learned. Therefore, it is important to be aware of stress management strategies to ensure a life free from stress-related health problems and a healthy lifespan.